The VBLUE queue management mechanism in video environment - Cao, Thang Diep; Nguyen, Hai Thuc; Nguyen, Giang Linh (Journal of Computer Science and Cybernetics, 2014)
The rapid development of video streaming applications over the internet poses a growing challenge. The requirements for bandwidth capacity and latency of transmission package often change constantly. One of the queue management mechanisms commonly used to increase the performance and prevent the degradation of video transmission quality is the active queue management mechanism (AQM). However, though the internet is a good effort network it does not have distinctions among transmission packets on the network leading to a significant percentage of video data packet discarded by the network router upon the occurrence of lacking bandwidth on the traffic lines due to congestion. The impact of the lost video package degrading the quality of watching at the receiver may vary from negligible to unacceptable levels. This paper proposes an innovative solution using selected VBLUE to discard the package which is built in the BLUE active queue management mechanism. The simulation results on NS-2 are given to show the efficiency of VBLUE for increasing the significant quality of video streaming.